Evaluation of Aconitum diterpenoid alkaloids as antiproliferative agents. Issue 7 (1st April 2015) - Wada, Koji; Ohkoshi, Emika; Zhao, Yu; Goto, Masuo; Morris-Natschke, Susan L.; Lee, Kuo-Hsiung
Graphical abstract: Abstract: Little information has been reported on the antitumor effects of the diterpenoid alkaloid constituents of Aconitum plants, used in the herbal drug 'bushi'. This study was aimed at determining the antitumor activities of Aconitum C19 -and C20 -diterpenoid alkaloids and synthetic derivatives against lung (A549), prostate (DU145), nasopharyngeal (KB), and vincristine-resistant nasopharyngeal (KB-VIN) cancer cell lines. Newly synthesized C20 -diterpenoid alkaloid derivatives showed substantial suppressive effects against all human tumor cell lines tested. In contrast, natural and derivatized C19 -diterpenoid alkaloids showed only a slight or no effect. Most of the active compounds were hetisine-type C20 -diterpenoid alkaloids, specifically kobusine and pseudokobusine analogs with two different substitution patterns, C-11 and C-11, 15. Notably, several C20 -diterpenoid alkaloids were more potent against multidrug-resistant KB subline KB-VIN cells. Pseudokobusine 11-3′-trifluoromethylbenzoate (94 ) is a possible promising new lead meriting additional evaluation against multidrug-resistant tumors.